The Changing Status of German Reunification in Western Diplomacy, 1955-1966 - Planck, Charles R. (Johns Hopkins University Press, 1967)
This book reviews the course of NATO policy on German reunification from the perspective of West German preferences and Bonn's endeavors to have them respected in the diplomatic efforts of the major allies. With its accession to NATO, the West German government under Adenauer continued its policy of rehabilitating the German people in the eyes of the Western political community by playing a willing and sometimes leading role in joint ventures whose purpose was said to transcend the nation-state.